9th North American Caribou Workshop, 23-27 April 2001, Kuujjuaq, Québec, Canada. - Haugerud (ed. in chief), Rolf Egil; Couturier, Serge; Ginhoven (iss. eds.), Quentin van (Rangifer, 2003)
From April 23 to 27, 2001, more than 230 caribou experts migrated to the 9th North American Caribou Workshop, held at the treeline in the Inuit town of Kuujjuaq, Nunavik, Québec.